International practice in vaccination of pregnant women against pertussis (a review) - S. M. Kharit; Yu. E. Konstantinova (Журнал инфектологии, 2021)
Whooping cough is still an urgent health problem in Russia, despite the vaccination that has been carried out for many decades. The group at high risk of severe whooping cough and death from it is children under 1 year old who have not received routine vaccination or are not vaccinated by age (the first months of life). The world health organization recognizes vaccination of pregnant women as the most effective method of preventing whooping cough in children before they receive three routine vaccinations. World experience in immunization programs for pregnant women against pertussis shows that up to 91% of children under 3 months of life are protected from pertussis as a result of transplacental transmission of antibodies formed in the mother after her vaccination (which corresponds to the timing of vaccination of children against pertussis in Russia: the first vaccination at the age of 3 months). The maximum preventive effect for a child was observed when a pregnant woman was immunized at 28–32 weeks of gestation. The safety of vaccination for both mother and child is shown. No serious adverse events related to vaccination have been reported. Coverage of pregnant women with vaccination in different countries reaches 51-70%. In order to increase adherence to vaccination of pregnant women, medical personnel should be regularly trained in the basics of vaccination, as well as conduct active health education among the population.